2017
DOI: 10.1155/2017/1910450
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Protects Human Lens Epithelial Cells against Oxidative Stress‐Induced Damage

Abstract: Oxidative stress has been recognized as an important mediator in the pathogenesis of age-related cataracts; using antioxidant supplements is one plausible strategy to protect the antioxidative defense system against oxidative stress. Ghrelin administration is expected to reduce ROS, preventing the onset of different diseases. The role of ghrelin, if any, in protecting against oxidative stress in HLECs has never been examined. In the present study, we investigated the effects of ghrelin against H2O2-induced oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…These results were also validated in the lens anterior capsules of cataract patients compared with normal lens anterior capsule samples. Although the increased levels of caspase-1 may indicate the involvement of pyroptosis in the process, it is difficult to distinguish between apoptosis and pyroptosis as apoptosis has also been reported to be involved in cataract formation in H 2 O 2 -treated lens epithelial cells (29). Therefore, further studies are required to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…These results were also validated in the lens anterior capsules of cataract patients compared with normal lens anterior capsule samples. Although the increased levels of caspase-1 may indicate the involvement of pyroptosis in the process, it is difficult to distinguish between apoptosis and pyroptosis as apoptosis has also been reported to be involved in cataract formation in H 2 O 2 -treated lens epithelial cells (29). Therefore, further studies are required to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Although the increased expression of caspase-1 and GSDMD and the inhibitory activity of caspase-1 indicate that pyroptosis may be involved in the cataract formation under SWBL exposure, pyroptosis and apoptosis are still di cult to distinguish. It has been reported that apoptosis is involved in cataract formation 18 . Multiple studies show that the characteristic morphological changes of various types of cell death are cell rounding and shrinkage in apoptosis, intact cell membrane and vacuolated cytoplasm in autophagy, and the appearance of membrane bubbles or swelling in pyroptosis [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis and apoptosis depend on particular caspases to motivate their separate programmed cell death pathways. Pyroptosis can be caused by both canonical and noncanonical in ammasome signalling pathways [15][16][17][18][19][20][21]. Caspase-1, which leads to the cleavage of GSDMD and induces pore opening on the cytomembrane [22][23][24], can activate canonical in ammasome signalling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…It is not determined whether this inflammatory protection is due to an increase in both AG and DAG via increased GHRL expression, or whether is the result of a shift in DAG or AG concentrations. Previous studies have linked AG with a plausible role in protecting human lens epithelial cells [36] and osteoblastic cells [37] against reactive oxygen species accumulation. In addition to AG, DAG treatment has also established a protective role from oxidative stress in microvascular endothelial cells via regulation of sirtuin 1 (SIRT1) catalytic activity [38] and within osteoblastic cells independent of GHSR1α [37].…”
Section: Discussionmentioning
confidence: 99%